Effect Of Organization Commitment Mediation To Organizational Citizenship Behaviors With Interpersonal Communication And Work Satisfaction As Antesedent Variable - Ramdani Bayu Putra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2018)
The purpose of this research is to know and analyze the effect of mediation of organizational commitment to organizational citizenship behaviors (OCB) with interpersonal communication and job satisfaction as antecedent variable. Population and sample of this research is all employees of Regional Disaster Management Agency of West Sumatera Province which amounted to 52 people. The sampling technique used the census method.The results of Structural Equations Modeling (SEM) testing with SmartPLS 2.0 M3 show significant positive influences of interpersonal communication, job satisfaction and organizational commitment to organizational citizenship behaviors (OCB). Furthermore, the results of the analysis also concluded that there is a significant positive effect of interpersonal communication and job satisfaction on organizational commitment. As for the indirect influence of the results of this study, proving that organizational commitment is able to strengthen or enhance the influence of interpesonal communication and job satisfaction on organizational citizenship behaviors.Keywords : Interpersonal Communication, Job Satisfaction Organizational Commitment, and Organizational citizenship behaviorsAbstrakTujuan penelitian ini adalah untuk mengetahui dan menganalisis efek mediasi komitmen organisasi terhadap organizational citizenship behaviors (OCB) dengan komunikasi interpersonal dan kepuasan kerja sebagai variabel anteseden. Populasi dan sampel penelitian ini adalah seluruh Pegawai Badan Penanggulangan Bencana Daerah Provinsi Sumatera Barat yang berjumlah sebanyak 52 orang. Teknik pengambilan sampel menggunakan metode sensus.Hasil pengujian Structural Equations Modeling (SEM) dengan SmartPLS 2.0 M3, memperlihatkan terdapat pengaruh positif yang signifikan komunikasi interpersonal, kepuasan kerja dan komitmen organisasi terhadap organizational citizenship behaviors (OCB). Selanjutnya hasil analisis juga menyimpulkan terdapat pengaruh positif yang signifikan komunikasi interpersonal dan kepuasan kerja terhadap komitmen organisasi. Sedangkan untuk pengaruh tidak langsung hasil penelitian ini, membuktikan bahwa komitmen organisasi mampu memperkuat atau meningkatkan pengaruh komunikasi interpesonal dan kepuasan kerja terhadap organizational citizenship behaviors.Kata Kunci : Komunikasi interpersonal, Kepuasan kerja Komitmen organisasi, dan Organizational citizenship behaviors